Предмет:
МатематикаАвтор:
анонимcos^2a + sin^2a = 1;
sin2a = 2 * sina * cosa;
cos2a = cos^2a - sin^2a;
1 - cos2α / sin2α = (1 - cos^2a + sin^2a) / 2 * sina * cosa =
= (cos^2a + sin^2a - cos^2a + sin^2a) / 2 * sina * cosa =
= sina / cosa = tga.
Ответ: 1 - cos2α / sin2α = tga.
Автор:
chicoДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть